Ensaios sobre Inflação, dinâmica produtiva e política econômica em uma abordagem estruturalista pós-Keynesiana - Antônio Cláudio Lopes da Gama Cerqueira (2016)
"In the essays are analyzed, in a theoretical and empirical perspective, the characteristics of the equations of the canonical model of inflation, productive dynamic and economic policies in the Post-Keynesian approach -- the Extended Post-Keynesian Model (EPKM). In the first essay is proposed the Structuralist Phillips Curve from the markup rule, forming a dynamic path in which inflation has partial inertia and varies with output gap, distributive conflict and external relations, being estimated in panels of countries after defining output gap by a formulation where trends are linearly divided into parts. As expected the parameter of past inflation has a value lesser than unity and the parameters of distributive conflict and external relations are relevant in all groups of countries and periods. In the second essay is proposed the Structuralist Output Gap Curve based on the Principle of Effective Demand, forming a dynamic path in which transitory deviations from the stochastic trend are related with 'accelerators' coming from consumption, public sector, financial sector and external sector, being estimated in panels of countries after defining output gap by the formulation where trends are linearly divided into parts. As expected the parameter of past output gap has a value lesser than unity and the parameters of accelerators are relevant in all groups of countries and periods, in special the extra spending of consumers. In the third essay is proposed the General Extended Post-Keynesian Model (GEPKM), an open system in which the dynamics of inflation and production have their own determinants, but related to each other through the stochastic rate of output growth. In the model, because there is no definite relationship between interest rate and output the policies impacts are captured by transmission channels expressly located in time and space, affecting processes in unknown degrees of magnitude and duration. The estimations attest a wide variability of policies impacts in countries and periods, basing the vision of an inherently unstable system displaying path-dependent trajectories. To posterior development is proposed multivariate filters adding conditional information from external constraints, industry characteristics, financial constraints, technical progress induced by demand, among others, with the aim of improving the calculation of the synthetic variable of productive dynamic inserted in inflationary dynamic. At last, considering the importance of distributive conflict in inflation path, is suggested an income policy with the explicit concern of mitigation on inflation's impacts, emphasizing the political challenge of achieving consensus in the complex relationship there is between social classes in capitalism."